Der Dritte Weg auf dem Prüfstand - Theologische, rechtliche und ethische Perspektiven des Ideals der Dienstgemeinschaft in der Diakonie - Hermelink, Jan (Universitätsverlag Göttingen, 2006)
For risks and side effects ask your doctor, pharmacist - or the Clinical Ethics Committee in your environment." The establishment of clinical ethics committees is a direct response to the professionalization of the medical establishment and the achievements in medical technology. Always progress in medicine was more than just technological advance. Especially its undeniable successes face doctors, nurses, chaplains and the management at the same time with new questions and problems. With the institutionalization of clinical ethics consultation connects the expectation of understanding the complex processes on a common basis. What taks are set for ethics committees in hospitals? How becomes ethic an issue there? And how do theologians and nurses communicate in these bodies? These papers summarize from a theological and philosophical point of view central research findings discussed in the framework of the DFG-funded research project "Ethics and Organisation